Structural relationships between emotional intelligence, well-being, and psychological distress: a multi-group SEM study among undergraduate physical education students in three Arab countries - Zayed, Kashef; Omara, Ehab; Al Kitani, Mahfoodha; Al-Yaaribi, Ali; Al-Jadidi, Khalifa; Daroushi, Abdul Rahim; Al Busafi, Majid; Gaafar, Amin; El-Ashkar, Heba; Al-Hadabi, Badriya; Ali, Ezzedin (Frontiers in Psychology, 2025)
BackgroundEmotional intelligence (EI) has been consistently associated with higher levels of psychological well-being (WB) and lower levels of psychological distress (PD). Yet, relatively little is known about how these relationships operate within Arab cultural contexts, especially among students training to become professionals in fields that promote both mental and physical health. Given the growing recognition of mental health challenges among youth in the region, examining these associations within Arab university settings is both timely and important. This study aimed to investigate how EI, WB, and PD are connected in undergraduate physical education students from Oman, Kuwait, and Jordan. It also examined whether WB helps explain the link between EI and PD and whether the proposed model holds consistently across these different cultural settings.MethodsA cross-sectional survey design was used with a sample of 788 undergraduate physical education students. Participants completed validated self-report measures assessing EI (five theoretically grounded dimensions: Self-Awareness, Empathy, Self-Regulation, Social Regulation, and Emotional Control), psychological well-being (Short Warwick-Edinburgh Mental Well-Being Scale), and psychological distress (Depression, Anxiety, and Stress Scale). Confirmatory Factor Analysis (CFA) evaluated the measurement models, and Structural Equation Modeling (SEM) tested direct and indirect relationships. Multi-Group Confirmatory Factor Analysis (MGCFA) examined measurement invariance across the three countries. To provide a more comprehensive picture of the associations, Pearson correlations and multiple regression analyses were also conducted.ResultsCFA confirmed the validity and reliability of the measures across all three samples. The SEM results indicated that EI was directly and positively related to WB, and indirectly related to PD through the mediating effect of WB. While configural and metric invariance were established, scalar invariance was not, limiting mean-level comparisons across countries. Nonetheless, the achieved invariance allowed valid structural analyses. Mediation analysis revealed that WB significantly mediated the EI– PD relationship in Kuwait, but not in Oman or Jordan. These findings suggest that the strength and direction of psychological mechanisms may vary by cultural context.ConclusionThe study highlights the positive role of EI in enhancing well-being and reducing psychological distress among university students in Arab contexts. However, the pathways linking these constructs may differ across cultural settings. Practical implications include the integration of emotional intelligence development into university curricula, particularly in disciplines that emphasize both mental and physical health. These findings emphasize the need for culturally sensitive approaches to emotional intelligence training and mental health promotion, especially for students preparing to serve as future educators and health professionals.